Design and Developing of Bullock Drawn Multi-Purpose Implement for Sandy Loam Soil - Chandegara, V K (Journal of Agricultural Engineering, 2003)
A study has been carried out to develop a multipurpose pipe frame implement for tillage, sowing, interculturing and digging operations in sandy loam deep soils of middle Gujarat Agro-climatic Zone-III. During the field testing, cost of cultivation was Rs.2063.88/ha for local implements, while for the multipurpose implement it was Rs. 1471.17/ha. Thus multipurpose implement save, Rs.592.71/ha in addition to time and 52. 19 % lower investment over traditional implement. The hourly cost of a pair of bullock was Rs.39.62.